The Effect of Well-Star Psycho-Education Program on Wellness and Psychological Symptom - Kayi̇ş, Ahmet Rıfat; Ceyhan, Aydoğan Aykut (Türk Psikolojik Danışma ve Rehberlik Derneği, 2020)
The aim of this study is to investigate the effects of the Well-Star Psycho-Education Program (WS-PEP) on the levels of wellness (general, physical, emotional, social, cognitive, and target-oriented and making sense of life) and psychological symptoms. A 3x3 experimental design including pre-test, post-test and follow-up measurements with experimental, placebo and control group was used. The Well-Star Scale and Brief Symptom Inventory were used to collect the data of the study. In addition, qualitative data was collected through focus group interview. The quantitative findings showed that WS-PEP had no significant effect in increasing wellness. However, the findings of the focus group interview with the six students in the experimental group have shown that students believed they acquire new skills to improve their wellness. It was also found that WS-PEP was effective in reducing the psychological symptom levels of university students and this effect continued to be observed during the follow-up process.
Keywords: Psikoloji; Psychology; Wellness; Psychological Symptoms; Psycho-education; Well-star Model; Counseling; 4. Education; 3. Good health